Collection of in-field impact loads acting on a rugby wheelchair frame - Bettella, F.; Magrini, M. L.; Petrone, N. (Proceedings, 2018)
This work was included in a wider project oriented to the improvement of residual neuromuscular skills in disabled athletes playing wheelchair rugby: the wheelchair rugby Italian national team was involved and tests allowed to analyse the impact loads on a rugby wheelchair frame. The frame of a rugby wheelchair offensive model, made by OffCarr Company, was instrumented with four strain gauge bridges in four different points. Then, three test types were conducted in laboratory: two static calibrations with the application of known loads, the first with horizontal load and the second with vertical load, and a dynamic horizontal calibration, impacting against a fix load cell in order to validate the results of horizontal static calibration. Finally, a test session took place in the field with the collaboration of two team players. The test consisted in voluntary frontal impacts between the two players, starting from 6 meters distance each other. The opponent of the instrumented wheelchair was a defender. From this test, the value of the horizontal load received by the frame in the impact instant was quantified. Moreover, also the vertical load acting on the wheelchair during the rebound of the player after the hit was evaluated: these informations were useful to the wheelchair frame manufacturer for the proper static, impact and fatigue design.